Marinduque 2050: Scanning the Futures of Safety and Security, Policing, and Law Enforcement in the Province of Marinduque - Hermosa, Portia Recinto; Mendoza, Danilo Gumia; De Mesa, Katrina Evangelista; Dausan, Alrien F. (Future Science / FSH-PH Publications, 2025)
This study was conducted to determine the Marinduque Safety and Security Futures Scenarios, aiming to identify areas for knowledge co-creation and sharing among stakeholders regarding safety and security. A focus group discussion was utilized to determine the ecosystem that exists among the participants through the identification of (a) the current trends, issues, and challenges on public safety and security in the Province of Marinduque; (b) determine the strategies, initiatives, practices, and actions taken by law enforcement agencies; (c) identify the potential blockers and areas for collaboration among the stakeholders; and (d) craft a futures scenario for the public safety and security. The domains of the focus group discussion are (1) Environmental Protection, (2) Maritime Law Enforcement, (3) Disaster Resilience, (4) Sexual Abuse, and (5) Community Participation were revealed to be potential blockers for Marinduque 2050 but also something that can be proactively through the integration of Routine Activity Theory, collaborating among the town and gown, further exposing a need for a whole-society approach.